Pengaruh Edukasi Tanggap dalam Menghadapi Gempa Bumi terhadap Persepsi Risiko dan Sikap Kesiapsiagaan Bencana Gemba Bumi di Yayasan Rumah Piatu Muslim Jakarta Pusat Tahun 2024 - Johara, Johara; Wicaksono, Hendik (Jurnal Riset Hesti Medan, 2024)
Earthquakes are a type of natural disaster that can occur at any time of the year, day or. night. Their negative impacts occur suddenly, and there are few warning signs. Children are one of the most vulnerable groups when a disaster occurs. They have limited skills and resources to control and prepare themselves when they feel afraid. Risk perception includes an evaluation of the possibilities and negative consequences of a risk. Preparedness refers to a series of actions to prevent disasters through appropriate and effective organizations and procedures. The approach used in this research is a quantitative approach. The research method used is quasi-experimentation. The respondents were 32. The instrument used in this research is a questionnaire. Variable X was measured using a pretest questionnaire. Variable Y was measured using a posttest questionnaire. This research uses the Wilcoxon statistical test with a value of α = 0.05, or 95%. The statistical test results show values of 0.006 and 0.064. The conclusion of this research is that there is an influence between responsive education in dealing with earthquakes on risk perception and earthquake disaster preparedness attitudes at the Muslim Orphanage Foundation in Central Jakarta in 2024. Discussion: For respondents, it is necessary to increase their knowledge regarding risk perception and earthquake disaster preparedness by looking for various information from trusted sources so they can always be prepared when an earthquake occurs.